178k views
1 vote
3x - 5y = -2

2x + y = 3
A) Multiply first equation by -3 and second equation by 2, solution (1, 1).
B) Multiply first equation by -2 and second equation by 3, solution (1, 1).
C) Multiply first equation by -3 and second equation by 2, solution (1, -1).
D) Multiply first equation by -2 and second equation by 3, solution (1, -1).

1 Answer

2 votes

Option B

Multiply first equation by -2 and second equation by 3, solution (1, 1)

Solution:

Given system of equations are:

3x - 5y = -2 -------- eqn 1

2x + y = 3 ------- eqn 2

We have to solve the system of equations

Multiply eqn 1 by -2

-6x + 10y = 4 ------- eqn 3

Multiply eqn 2 by 3

6x + 3y = 9 -------- eqn 4

Add eqn 3 and eqn 4

-6x + 10y = 4

6x + 3y = 9

( + ) ------------

13y = 13

y = 1

Substitute y = 1 in eqn 2

2x + 1 = 3

2x = 2

x = 1

Thus solution is (1, 1)

Thus option B is correct

User Fabian Ying
by
5.5k points